The Role of Dayah Salafiyah in the Development of Religious Culture in Langsa - Fakhrurrazi Fakhrurrazi; Hasan Asari; Erawadi Erawadi (STAI Hubbulwathan Duri, 2021)
Dayah sustainably transmits religious, intellectual, and spiritual traditions (Islamic Boarding Schools). Several Dayah Salafiyah in Langsa City, for example, are also involved in implementing and developing strategies for the cultivation of such religious cultures. To conduct a deeper examination, this phenomenological study examined the involvement, implementation, and strategies used in those Dayahs. Observations were used to collect data. Meanwhile, the data were organized using Miles and Huberman's qualitative data analysis framework. The findings indicated that religious activities based on religious culture at the Dayah Salafiyah in Langsa City were always developed in collaboration with the dayah's leaders, teungku dayah, santri, and community. To begin, the dayah's leader serves as a facilitator, motivator, and mediator in the students' and community's religious activities and a controller of the dayah's activities. Additionally, it is critical to remember that the most fundamental form of salafiyah dayah implementation promotes good behaviour. To ensure that the religious culture development program is carried out as planned, salafiyah education incorporates religious culture into all aspects of its operations. This strategy for religious culture development is carried out by establishing policies, habituation, and student awareness, exemplary behaviour, discipline, and civilization. The dayah's leaders have absolute authority to monitor and evaluate all efforts made by teachers and students to foster a strong religious culture in the school.